Стимулирующее влияние нитрата натрия на формирование посттравматических спаек у самок крыс = The stimulating effect of sodium nitrate on the formation of post-traumatic adhesions in female rats - Volyanska, A. G. (Journal of Education, Health and Sport, 2016)
Volyanska A. Стимулирующее влияние нитрата натрия на формирование посттравматических спаек у самок крыс = The stimulating effect of sodium nitrate on the formation of post-traumatic adhesions in female rats. Journal of Education, Health and Sport. 2016;6(1):315-326. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45398 http://ojs.ukw.edu.pl/index.php/johs/article/view/3366 https://pbn.nauka.gov.pl/works/710938 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. УДК 617.55-001-007.274-092.9-02:549.751.11 СТИМУЛИРУЮЩЕЕ ВЛИЯНИЕ НИТРАТА НАТРИЯ НА ФОРМИРОВАНИЕ ПОСТТРАВМАТИЧЕСКИХ СПАЕК У САМОК КРЫС The stimulating effect of sodium nitrate ON THE FORMATION OF post-traumatic ADHESIONS in female rats А. Г. Волянская A. Volyanska Одесский национальный медицинский университет, Одесса Odessa National Medical University Summary Rationale of the present article is stipulated by the fact that the role of nitrates - the main product of oxidation of NO in the pathogenesis of post-surgical adhesions formation is not well understood. The objective - to study the peculiarities of the formation of post-traumatic adhesions in rats at the background of long-term appointment of sodium nitrate aqueous solution. In the group of animals treated with talc, moderate signs of inflammation of the uterus, manifested in a diffuse lymphoplasmacytic infiltration, hyperemia of blood vessels and perivascular edema myometrium, against the backdrop of a distinct inflammatory reaction and fibrosis of the rectum have been recorded. It was found that the use of sodium nitrate in the experiment has a stimulating effect on the formation of post-traumatic adhesions. While prosecting of abdominal cavity adhesions occurred in 8 animals (80%) (95% CI: 55.20-104.79), OR = 36.00 (95% CI: 2.72-476.29). As a result of the analysis of ROC-AUC 0.61 (95% CI: 0.08-1,0). The pronounced manifestation of inflammatory responses by inducing a mild uterine fibrosis and remodeling of blood vessels body has been determined. Combined designation of talc and sodium nitrate also leads to bowel tissue sclerosis and significant strengthening of inflammation. The experiment carried out allowed to identify the main pathogenetic stages of development of adhesions, such as inflammation, angiogenesis and the formation of connective tissue elements. Keywords: adhesive process, white rat, uterus, sodium nitrate. Реферат Актуальность темы обусловлена тем, что роль нитратов – основного продукта реакций окисления NO в патогенезе постхирургического спайкообразования изучена недостаточно. Цель работы – изучить особенностей формирования посттравматических спаек у крыс на фоне продолжительного назначения водного раствора нитрата натрия. В группе животных, получавших тальк, регистрируются умеренные признаки воспаления тканей матки, проявляющиеся в диффузной лимфоплазмоцитарной инфильтрации, гиперемии кровеносных сосудов миометрия и периваскулярном отеке, на фоне четко выраженной воспалительной реакции и фиброза прямой кишки. Установлено, что применение в эксперименте нитрата натрия оказывает стимулирующее влияние на процесс образования посттравматических спаек. При вскрытии брюшной полости спаечный процесс имел место у 8 животных (80%) (95% ДИ : 55,20-104,79), ОШ = 36,00 (95% ДИ : 2,72-476,29). По результатам ROC-анализа ППК 0,61 (95% ДИ 0,08-1,0). Определяется ярко выраженная манифестация воспалительных реакций, индуцируя умеренный фиброз матки и ремоделирование кровеносных сосудов органа. Комбинированное назначение крысам талька и нитрата натрия также приводит к склерозированию тканей кишечника и существенному усилению признаков воспаления. Проведенное экспериментальное исследование позволило определить основные патогенетические этапы развития спаечного процесса, такие как, воспалительный процесс, неоангиогенез и образование элементов соединительной ткани. Ключевые слова: спаечный процесс, белые крысы, матка, нитрат натрия.